Transcatheter aortic valve implantation in moderate bicuspid aortic valve disease in a patient with end-stage dilated cardiomyopathy – bridge to heart transplantation - Mizia-Szubryt, Magdalena; Hudziak, Damian; Grabka, Marek; Małyszek-Tumidajewicz, Justyna; Wojakowski, Wojciech; Mizia-Stec, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 64-year-old patient with dilated cardiomyopathy (DCM) and chronic heart failure with reduced ejection fraction (HFrEF), with an implanted cardioverter-defibrillator, was admitted to the cardiology unit due to consecutive acute heart failure (HF) decompensation. Regardless of potent optimal pharmacotherapy, at admission, the patient was in NYHA class 4.